Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3109/0886022x.2014.927771
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a continuous quality improvement program reduces the occurrence of peritonitis in PD

Abstract: Objective: To investigate the causes of peritonitis in patients with peritoneal dialysis (PD) using continuous quality improvement (CQI) to develop effective interventions and reduce the occurrence of peritonitis. Methods: A quality control team consisting of 10 members, including the department head, four nephrologists and four nurses, all specialized in PD care, and the head nurse, was established at the Peritoneal Dialysis Center of the Third Xiangya Hospital of Central South University. All patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 8 publications
(8 reference statements)
0
18
0
1
Order By: Relevance
“…For example Yu and others reported that a PD CQI program improved the rate of peritonitis from 1 episode in 22.2 patient-months to 1 episode in 30.1 patient-months in the first year after implementation and, subsequently, to 1 episode in 71.1 and 77.3 patient-months in years 2 and 3, respectively (16). Wang and others reported a reduction in the incidence of peritonitis from 1 in every 40.1 patient-months before the CQI to once every 70.8 patient-months after CQI (15). The PD CQI program described in this study did not differ substantially in its components from other PD CQI programs that have been described in the literature (11,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…For example Yu and others reported that a PD CQI program improved the rate of peritonitis from 1 episode in 22.2 patient-months to 1 episode in 30.1 patient-months in the first year after implementation and, subsequently, to 1 episode in 71.1 and 77.3 patient-months in years 2 and 3, respectively (16). Wang and others reported a reduction in the incidence of peritonitis from 1 in every 40.1 patient-months before the CQI to once every 70.8 patient-months after CQI (15). The PD CQI program described in this study did not differ substantially in its components from other PD CQI programs that have been described in the literature (11,(14)(15)(16).…”
Section: Discussionmentioning
confidence: 60%
“…Wang and others reported a reduction in the incidence of peritonitis from 1 in every 40.1 patient-months before the CQI to once every 70.8 patient-months after CQI (15). The PD CQI program described in this study did not differ substantially in its components from other PD CQI programs that have been described in the literature (11,(14)(15)(16). While these types of programs exist elsewhere, they have not previously been examined for economic impact.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…If a pattern of infections develops, the team should investigate and plan interventions to rectify the problem. Observational data suggest that CQI programs reduce peritonitis rates and improve technique survival (17,(153)(154)(155). However, none of these studies reported catheter-related infection as an outcome measure.…”
Section: Continuous Quality Improvementmentioning
confidence: 99%